FUEL PROPERTIES AND DIESEL ENGINE EXHAUST GAS TEMPERATURE OF BIODIESEL-CALOPHYLLUM INOPHYLLUM-ESSENTIAL OIL MIXTURE - Gamayel, Adhes; Priyadi, Muhammad Untung Zaenal (Jurnal Dinamika Vokasional Teknik Mesin, 2024)
This research investigates the properties and performance of fuel blends comprising biodiesel, Calophyllum inophyllum oil (Nyamplung), and essential oils. Biodiesel, a renewable energy source, has gained significant attention due to its low sulfur content, high calorific value, and biodegradability. Experimental investigations involved blending biodiesel with Nyamplung oil and essential oils (clove oil, pine oil, and turpentine oil) in varying proportions. Fuel properties, including density, viscosity, and flash point, were analyzed to assess combustion characteristics. Additionally, engine performance parameters such as torque and exhaust gas temperature (EGT) were evaluated to understand combustion efficiency and engine health. The results revealed that the addition of Nyamplung oil and essential oils increased the density and viscosity of the fuel blends compared to pure biodiesel, impacting atomization and combustion processes. Despite higher viscosity potentially causing ignition delay, flash points decreased due to the presence of essential oils, enhancing safety during storage and handling. Torque measurements indicated variations in engine performance among fuel mixtures, with incomplete combustion observed in blends containing essential oils. EGT measurements further highlighted differences in combustion completeness, with lower temperatures observed in pure biodiesel due to improved atomization and complete combustion.